Big Data for Creating and Capturing Value in the Digitalized Environment: Unpacking the Effects of Volume, Variety, and Veracity on Firm Performance*. Issue 1 (29th August 2020) - Cappa, Francesco; Oriani, Raffaele; Peruffo, Enzo; McCarthy, Ian
Abstract : Despite significant academic and managerial interest in big data, there is a dearth of research on how big data impacts the long‐term firm performance. Reasons for this gap include a lack of objective indices to measure big data availability and its impact, and the tendency of studies to ignore the costs associated with collecting and analyzing big data, assuming that big data automatically delivers benefits to firms. Focusing on how firms create and capture value from big data about customers, we use the resource‐based view and three dimensions of big data (i.e., volume, variety, and veracity) to understand when the benefits outweigh the costs. Relying on the number of downloads of mobile device applications, we find that volume of big data has a negative effect on firm performance. This result suggests that the "bigness" of big data alone does not ensure value creation for a firm, and could even constitute a "dark side" of big data. Because big data variety—measured as the number of types of information taken per each application—moderates the negative effects of big data volume, simultaneous high values of volume and variety allow firms to create value that positively affects their performance. In addition, high levels of veracity (i.e., a high percentage of employees devoted to big data analysis), are linked to firms benefiting from big data via value capture. These findings shed light on the circumstances in which big data can be beneficial for firms, contributing to a better theoretical understanding of the opportunities and challenges and providing useful indications to managers. Abstract :